How Do Men in Prison Manage Relationship with Their Female Partners? A Biographical Study of Repeat Offenders - Szczepanik, Renata (Przegląd Badań Edukacyjnych (Educational Studies Review), 2018)
The aim of this paper is to analyze the ways in which men in prison manage their relationships with female partners. Drawing on the theoretical perspective of dramaturgy and grounded theory methodology, the article presents an analysis of interviews with habitual offenders. The ways in which these offenders manage relationships with women are considered within a broader strategy of achieving a desired status among other inmates. The focus of the study is not on the interactions between men in prison and their female partners, but the interactions among men in prison. Specifically, the article identifies three interaction strategies for managing the relations with women – giving permission, breaking up and setting free. Each of these strategies encapsulates patriarchal values that the offender defends.